Starting working meeting on «Russian Register of Patients with ANCA-Associated Systemic Vasculitis» (28 April, 2014, Moscow) - Issue Editor (Научно-практическая ревматология)
Starting working meeting on «Russian Register of Patients with ANCA-Associated Systemic Vasculitis» (28 April, 2014, Moscow)